2018
DOI: 10.1097/rlu.0000000000002216
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT With Diffusely High FDG Uptake Throughout Subcutaneous Adipose Tissues

Abstract: A 9-year-old girl presented with facial rash, angioedema, fevers, and night sweats. She was diagnosed with chronic active Epstein-Barr virus infection and placed on chronic steroid treatment. F-FDG PET/CT performed 3 weeks following presentation revealed diffuse subcutaneous soft tissue FDG activation throughout the entire body, with likely localization to white subcutaneous adipose tissue. This highly unusual appearance may have been due to the patient being treated with corticosteroids at the time of the sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 6 publications
0
4
0
2
Order By: Relevance
“…Few recent studies have also shown increased 18 F-FDG uptake in the WAT. Kong and Nadel 3 reported these findings in a case of Epstein-Barr virus and Pattison et al 4 also described similar findings in case of non–small cell lung carcinoma treated with corticosteroids. Hofman and Hicks 5 described similar results in a patient with recurrent cervical cancer who received intravenous ascorbic acid and insulin shortly before scan 5 .…”
mentioning
confidence: 67%
“…Few recent studies have also shown increased 18 F-FDG uptake in the WAT. Kong and Nadel 3 reported these findings in a case of Epstein-Barr virus and Pattison et al 4 also described similar findings in case of non–small cell lung carcinoma treated with corticosteroids. Hofman and Hicks 5 described similar results in a patient with recurrent cervical cancer who received intravenous ascorbic acid and insulin shortly before scan 5 .…”
mentioning
confidence: 67%
“…Enhanced 18 F-FDG uptake in remodeled white adipose tissue has been sparsely reported in lymphoma patients receiving chemotherapy and glucocorticoids (1,2). It is well known that glucocorticoids play an important role in regulation of fat metabolism via stimulation of lipolysis, lipogenesis, and adipogenesis processes, which may lead to a classic Cushingoid distribution of central white adipose tissue, that is, moon face and buffalo back, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this presence of high anxiety may even cause false positives, as in the case of the uptake of the [18F]FDG-PET-CT. in muscles and brown fat [8][9][10] which leads to a decrease in image quality and therefore lower diagnostic performance.…”
Section: Methodsmentioning
confidence: 99%